O uso da Documentação Pedagógica pela CP para a formação docente - Pressinoti, Patricia dos Anjos (2022)
This research aims to identify training needs of pedagogical coordinators of Early Childhood education schools in the neighborhood of São Miguel about the meaning and uses of Pedagogical Documents (photos, videos and written reports) during teacher training processes, as we understand as instruments to provide information that support the writing of students’ Individual Learning Follow-up Report (Relatório de Acompanhamento da Aprendizagem Individual). Specific objectives were: (1) to identify guiding principles that must be used for analyzing Pedagogical Documents such as: appreciation for children’s capacities, teachers’ sensitive listening, babies’ and toddlers’ participation during documentation process, organization of learning contexts; (2) to discuss the importance of producing quality Pedagogical Documents, to support reflection, interpretation and planning of continuous experiences with babies and toddlers. We defend the use of Pedagogical Documents as a training strategy that is capable of supporting teachers’ reflection about children’s abilities and the writing of babies and toddlers’ development reports. Six pedagogical coordinators participated of this study. Theoretical framework was based on early Childhood education oficial documents, on authors that study the role of pedagogical coordinators in teacher training, such as Almeida and Placco, and on researchers that study Pedagogical Documents, such as Fochi, Rinaldi, Vecchi and Madalena Freire. Some of the findings of this research show: (1) the importance of the pedagogical coordinator’s acknowledgement of babies’ and toddlers’ abilities; (2) the use of Pedagogical Documents is relevant in teacher training; (3) the pedagogical coordinator has an important role in favoring the study of Pedagogical Documents; (4) the pedagogical coordinators’ training needs for the use of Pedagogical Documents. We expect that this study contribute with the debate of the use of Pedagogical Documents during the training process of Early childhood education teachers, so they are capable of making babies and toddlers the core of their actions